A qualitative exploration of Palestinian managerial leadership styles. (2015) - Adawi, Majed H.; Forbes, Judy C.; Potter, Dorothy O.
The purpose of this study is to investigate how Palestinian employees perceive the phenomenon associated with managerial leadership styles and worker turnover. A qualitative study was conducted and 20 employees were interviewed. A qualitative methodology was used to analyse the content. Nine core themes emerged from the data: motivating employees, sharing decision-making, fostering a creative work environment, trusting employees' capabilities, acknowledging performances and efforts, developing and promoting employees, attending workshops and conferences, giving instructions and expecting execution, and providing pay in return for work. Most participants (85%) believed that Palestinian managers provide instructions and workers execute policies. The majority of participants (90%) deemed that most Palestinian managers use financial rewards to encourage employees to complete work; however, those managers do not often use non-financial motives. Based on the findings, Palestinian managers adopt the transactional leadership style and overlook other effective leadership styles such as transformational leadership.